CULTIVATING RELIGIOUS MODERATION VALUES THROUGH MANGAJI TUDANG AT MA’HAD ALY IN SOUTH SULAWESI - Pamessangi, Andi Arif; Takwim, Mardi; Kaharuddin, Kaharuddin; Nazaruddin, Rezkiawati (Balai Penelitian dan Pengembangan Agama Makassar, 2024)
This study attempts to examine in more depth the learning with the Mangaji Tudang system as an effort to instill the values of religious moderation in students of Ma'had 'Aly in South Sulawesi, especially at Ma'had 'Aly DDI Mangkoso. Data collection in this study used three techniques, namely observation, interviews, and documentation. The results of this study indicate that Ma'had 'Aly DDI Mangkoso focuses on the field of Fiqh and its ushul (takhassus Fiqh wa Usuluhu). Learning carried out with the Mangaji Tudang model is a specialty of Ma'had Aly in South Sulawesi, including at Ma'had 'Aly DDI Mangkoso by means of a group of students listening to the teacher (anregurutta) reading, translating, explaining, and interpreting books, then each student will pay attention to making notes and giving meaning especially to words that are difficult to understand. The model of instilling religious moderation values through Mangaji Tudang learning is carried out by conveying wise messages that soothe the people and focus on the deepening of inclusive fiqh, the balance between aqli and naqli arguments, and strengthening the concept of washatiyah Islam. This research provides. This research will greatly contribute to the model of Islamic boarding school education, especially at the higher education level of Islamic boarding schools (Ma'had 'Aly) in teaching classical books that are integrated with the instillation of religious moderation values..